Mouse Zygotes Respond to Severe Sperm DNA Damage by Delaying Paternal DNA Replication and Embryonic Development - Gawecka, Joanna E. (Public Library of Science, 2013)
Mouse zygotes do not activate apoptosis in response to DNA damage. We previously reported a unique form of inducible sperm DNA damage termed sperm chromatin fragmentation (SCF). SCF mirrors some aspects of somatic cell apoptosis in that the DNA degradation is mediated by reversible double strand breaks caused by topoisomerase 2B (TOP2B) followed by irreversible DNA degradation by a nuclease(s). Here, we created zygotes using spermatozoa induced to undergo SCF (SCF zygotes) and tested how they responded to moderate and severe paternal DNA damage during the first cell cycle. We found that the TUNEL assay was not sensitive enough to identify the breaks caused by SCF in zygotes in either case. However, paternal pronuclei in both groups stained positively for γH2AX, a marker for DNA damage, at 5 hrs after fertilization, just before DNA synthesis, while the maternal pronuclei were negative. We also found that both pronuclei in SCF zygotes with moderate DNA damage replicated normally, but paternal pronuclei in the SCF zygotes with severe DNA damage delayed the initiation of DNA replication by up to 12 hrs even though the maternal pronuclei had no discernable delay. Chromosomal analysis of both groups confirmed that the paternal DNA was degraded after S-phase while the maternal pronuclei formed normal chromosomes. The DNA replication delay caused a marked retardation in progression to the 2-cell stage, and a large portion of the embryos arrested at the G2/M border, suggesting that this is an important checkpoint in zygotic development. Those embryos that progressed through the G2/M border died at later stages and none developed to the blastocyst stage. Our data demonstrate that the zygote responds to sperm DNA damage through a non-apoptotic mechanism that acts by slowing paternal DNA replication and ultimately leads to arrest in embryonic development.